Development of a Critical Thinking Assessment Instrument for Earth Changes in Elementary School Science Lessons - Nisa Us Sa'idah; Eko Handoyo; Supriyadi; Woro Sumarni (Journal of Environmental and Science Education, 2025)
This study aims to develop an assessment instrument for critical thinking skills in elementary school science lessons on the topic of Earth's changes, in the form of essay questions that are tested for validity and reliability. The measurement of critical thinking skills uses indicators based on Ennis' framework, which includes providing simple explanations, building basic skills, concluding, providing further explanations, and setting strategies and tactics. The subjects of this study were 28 students from SDN 02 Pekiringanalit, Pekalongan Regency. Data analysis techniques involved content validity testing using Aiken's index. The validity of the assessment instrument was tested using the Rasch Model with the Ministep program to determine validity, calculate reliability, and obtain Cronbach's alpha values. This research is developmental research that applies the 4D development model, simplified into three steps: define, design, and development. The results showed that the critical thinking assessment instrument in the form of essay test questions received an Aiken's content and language validity index of 0.96, which falls into the very valid category. The validity per item obtained an Aiken's index of 0.89, placing it in the high validity category. The item analysis using the Rasch Model yielded a person reliability coefficient of 0.69 and 0.72, which is in the sufficient category. The item reliability was 0.86 and 0.87, which is considered good, and the Cronbach's alpha was 0.77, also considered good.